MEANINGS INTERPRETATION IN THE 2010 DOO-WOPS & HOOLIGANS BRUNO MARS’ SONG ALBUM - Rahmadhani, Fachreza; Natsir, M.; Valiantien, Nita Maya (Fakultas Ilmu Budaya Universitas Mulawarman, 2019)
Songs could have impacts on the community. When Bruno Mars launched his first album the